The UNMANNED AERIAL VEHICLE (UAV) AIRCRAFT DESIGN GALAK-24 WITH AUTONOMOUS METHOD - Surono, Argo; Ashar, Imam; Huda, Muhamat Maariful (Pustaka Poltekad, 2021)
Abstract: Unmanned Aerial Vehicle is a type of aircraft that is controlled by a remote-control system via radio waves. UAV is an unmanned system (Unmanned System), which is an electro-mechanical-based system that can carry out programmed missions with the characteristics of a UAV that is able to fly without a pilot capable of controlling automatically and can run again by carrying several weapons or other tools. An autopilot is a mechanical, electrical, or hydraulic system that guides a vehicle without human intervention. The application of the Autonomous control system on the UAV is carried out by using Autonomous equipment in the form of components such as Flight Controller, GPS, Mission Planner Software and Telemetry. The number of parameters set by the observations made on the movement of the UAV when in Auto mode. The flight test used a square waypoint with a distance of 500 meters on each side. The UAV is able to fly in an Autonomous manner stably using a predetermined Waypoint. This is a pure experiment by means of tool testing and data collection that requires very high attention from the crew and results in fatigue.